First stage reconstruction following surgical excision of a large arteriovenous malformation of the lower lip and tongue - Jenisa Kamayana; I Adnyana; Agus Hamid; I Sanjaya (Медицина болю)
Arteriovenous malformations (AVMs) are rare congenital lesions caused by deformity of the blood vessels. Around half of the AVMs are found in the craniofacial area, presenting with a progressive high-